Great Cormorants Phalacrocorax carbo feed on larger fish in late winter. Issue 2 (3rd April 2018) - Lyach, Roman; Blabolil, Petr; Čech, Martin
ABSTRACT: Capsule: Great Cormorants Phalacrocorax carbo prey on larger fish in late winter compared to early winter. Aims: This study aimed to describe Cormorant diet and to discover whether prey size changed during winter. Methods: The diet of Cormorants was studied using regurgitated pellets collected from roosting places at the upper Elbe River, Czech Republic, during winter (from December to March). Results: The diet consisted of 24 fish species from 6 fish families. Roach Rutilus rutilus dominated in the diet (over 50% of biomass). Size of fish in the diet increased over time during the whole winter. Except for European Chub Squalius cephalus, the increased size applied for the majority of the most frequently consumed fish species: Roach, European Perch Perca fluviatilis and White Bream Abramis brama . Cormorants consumed mostly fish species of lower commercial and angling value. Conclusion: Fisheries management should reflect on the fact that competition for larger-sized fish is the highest in late winter and in early spring. For that reason, stocking of potentially vulnerable fish could be delayed to the time when overwintering birds leave the area and recreational fishing could be restricted in late winter.